2013
DOI: 10.1007/s00192-013-2145-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and variations of pelvic organ prolapse bother

Abstract: Introduction and hypothesis To determine if prolapse symptom severity and bother varies among non-Hispanic white, Hispanic, and Native American women with equivalent prolapse stages on physical examination. Methods This was a retrospective chart review of new patients seen in an academic urogynecology clinic from January 2007 to September 2011. Data were extracted from a standardized intake form, including patients’ self-identified ethnicity. All patients underwent a Pelvic Organ Prolapse Quantification (POP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
0
29
2
1
Order By: Relevance
“…This information gap includes lack of knowledge regarding its prevalence, barriers to care, health seeking behaviors and patient understanding of pelvic floor disorders. Prior work is limited to one study which describes the prevalence of urinary incontinence among women who were members of a South Dakota tribe [14] and another describing the level of bother American Indian women experience regarding pelvic organ prolapse compared to Hispanic and non-Hispanic white women [15]. …”
Section: Introductionmentioning
confidence: 99%
“…This information gap includes lack of knowledge regarding its prevalence, barriers to care, health seeking behaviors and patient understanding of pelvic floor disorders. Prior work is limited to one study which describes the prevalence of urinary incontinence among women who were members of a South Dakota tribe [14] and another describing the level of bother American Indian women experience regarding pelvic organ prolapse compared to Hispanic and non-Hispanic white women [15]. …”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the 2003 National Census and National Hospital Discharge Survey showed that the rate of undergoing prolapse surgery was 14.8/10,000 women for Caucasian women compared with 5.6/10,000 women for African-American women [16]. Among women with stage 2 prolapse, Hispanic and Native American women had a higher level of bother, as measured by the POP-DI, compared with non-Hispanic white women; however, this difference was not noted among women with ≥ stage 3 prolapse [17]. As our database could not determine the degree of prolapse, it is difficult to determine the significance of these racial differences in receiving care.…”
Section: Discussionmentioning
confidence: 96%
“…Subtle pelvic floor support changes affect women’s quality of life (Dolan et al, 2004) and sexual activity (Brubaker et al, 2008). Some studies have found a correlation of pelvic organ prolapse with Hispanic ethnicity (Swift et al, 2005), and Hispanic women report more bother from stage II pelvic organ prolapse than non-Hispanic White women (Dunivan et al, 2014). …”
Section: Background On a Sensitive Research Topic: Pelvic Organ Prolapsementioning
confidence: 99%
“…A translator makes “assumptions about meaning equivalence that make her analyst and cultural broker as much as a translator” (Temple & Young, 2004, p. 171). Ideally, translators share personal characteristics and life experience with those being interviewed, as well as a deep familiarity with the interview topic, context of the interviews, and culture of participants (Al-Amer, Ramjan, Glew, Darwish, & Salamonson, 2014; Brämberg & Dahlberg, 2013; Temple et al, 2006). Additional procedures to improve translation of interviews include involving a team of translators, cycles of translation and back-translation, documentation of translation decisions and phrases in a study-specific dictionary, and debriefing interviews with interpreters and translators after each interview and at the conclusion of the study (Lopez, Figueroa, Connor, & Maliski, 2008; Merry et al, 2011).…”
Section: Translationmentioning
confidence: 99%